Competition's new clothes : 20 short cases on rivalry between firms - Lévêque, François (Cambridge : Cambridge University Press, 2019)
Lévêque recounts twenty revealing tales of real-life rivalry between firms across diverse industries, including wine, skiing, opera, video games and cruise liners. These entertaining and insightful narratives are informed by recent advances in economics, factoring in the many forces driving competition, including globalization and innovation. Divided into four sections, the book covers competition and the market; competition and variety; competition through innovation; and competition and equality. Read together, these stories also serve as building blocks to address the issue of whether competition between firms has entered a new era of increased intensity. This book will appeal to anyone, from company executives to consumers, who are interested in the economics of contemporary industry and want to incorporate a grasp of competition into their everyday decision-making. This book can also be used as a supplementary text in courses in microeconomics, business economics and industrial organisation.
Title from publisher's bibliographic system (viewed on 04 Feb 2019).
Keywords: elektronické knihy; electronic books; Organizational behavior; Competition